Age Differences of Human Sphenoid Sinus Dimensions: a Comparative Study by Gross Anatomical Dissection and CT Scan Imaging - Mohammad Ahmad ABDALLA (Modern Medicine)
Introduction: The sphenoid sinus is a central skull cavity situated inside the sphenoid bone as a twin structure, separated by a complete bony septum. The aim of the study to measure the length, width, and height of human sphenoid sinus through dissection compared to CT scan images in different age groups of both genders. Methods: A prospective study of 360 human bodies including 110 dissected cadavers and 250 individuals with CT scan images during a period from January 2019 to February 2020. Results: In male cadavers, the mean value of length was (24.8±4.2) and (23.6±3.8) mm for right and left sides, while for females was (24.5±3.7) and (25.3±4.1) mm. Whereas, for CT cases were (25.4±3.1), (27.2±4.1), (21.3±4.2), and (24.4±3.8) mm respectively. Otherwise, the width was (15.8±3.2) and (19.2±4.5) mm for right and left sides in male cadavers; but for females was (18.2±3.8) and (22.7±3.7). In comparison to CT cases, were (19.6±4.1), (20.4±4.7), (17.3±5.2), and (19.2±5.6) mm respectively. In male cadavers, the height was (21.4±3.1) and (26.8±2.8) mm for right and left sides, while for females was (13.8±3.3) and (19.6±3.1) mm. Whereas, for CT cases were (16.7±2.5), (18.2±2.7), (14.6±2.9), and (15.8±3.3) mm respectively. Conclusion: Findings of both methods yield accurate anatomic sinus views, which may determine the age, gender, and race of alive or dead individuals.